Technology push and demand pull practices for achieving sustainable development in manufacturing industries. Issue 2 (12th January 2018) - Singla, Anuj; Ahuja, Inderpreet Singh; Sethi, APS
Abstract : Purpose: The purpose of this paper is to evaluate the significance of various technology push (TP) and demand pull (DP) practices substantial for achieving sustainable development in Indian manufacturing industries. The research crucially examines the effectiveness of TP-DP practices in manufacturing companies. Design/methodology/approach: An extensive survey of 92 companies in India has been executed to identify improvements made by TP-DP practices, to achieve sustainable development in manufacturing industries. The companies in the survey include medium- and large-scale manufacturing enterprises. The correlations between various TP-DP practices and sustainable development parameters are evaluated and validated using various numerical methods and tools. Findings: The focus of the paper is on the distinguishable contributions made by TP-DP practices like innovative capability, research and development, corporate strategy, export orientation, stringent implementation of government regulations, transforming capabilities, unionized labor and customer attributes toward achieving sustainable development in manufacturing industries. The inter-relationships between different TP-DP practices with sustainable development parameters are evaluated to effectively manage the goals and objectives of industries related to sustainability and growth. However, it is also acknowledged that manufacturing firms need to work more actively on managing certain practices of TP-DP. Research limitations/implications: In the present investigation, contributions made by TP-DP practices are evaluated to accomplish sustainable development in Indian manufacturing industries. Hence, the results obtained may need some modifications before applying to other countries. Moreover, issue-wise independent modeling can also be performed to assess the importance of TP-DP practices under specific orientations. Practical implications: The research gives priority to enhancement in the planning among various TP-DP practices and sustainable development indicators in the industries, to impart TP-DP as important practices to meet the challenges of competent markets worldwide. Social implications: It has been exhibited from the observations that adequate TP-DP practices can efficiently contribute toward recognition of sustainable development to compete in the highly progressive global market. The results of various inter-relationships among TP-DP practices and sustainable development parameters represent the effectiveness of TP-DP practices for accomplishment of social as well as organizational objectives. Originality/value: The investigation shows that TP-DP practices are significant initiatives employed by the manufacturing industries for performance improvement and sustainable development. The paper peeks into the research to find out TP-DP issues that need to be assessed efficiently by companies to avail the benefits of sustainable development to meet the challenges posed by international markets.